The determination of qualification criteria in public procurement law: a comparative analysis between South Africa and Germany - Jonathan, Möller (Department of Commercial Law, 2025)
This dissertation compares South African and German public procurement law and their definitions of qualification criteria. In order to compare the two systems, it is essential to understand both procurement law systems with regard to their application, basic principles, objectives and challenges. Qualification criteria are essential in the procurement procedure and seek to determine the suitability of bidders. This involves checking whether the bidder is able to properly perform the subsequent contract. The criteria relate to, for example, the bidder's experience, personnel, technical capacities or company values. In addition to the primary objectives of the specific contract, secondary objectives can also be pursued using the award procedure, particularly when defining qualification criteria. Secondary objectives are, for example, social or sustainability objectives. In South Africa, this applies particularly to the area of black economic empowerment. In Germany, secondary objectives may be climate and environmental protection. Both procurement law regimes are subject to constant change, especially at present. In South Africa, the draft Procurement Bill was adopted on 16 May 2024 and became law as the Public Procurement Act on 23 July 2024. There will be a review process over the next two years that may bring changes. In Germany, the reform of procurement law is being discussed. The determination of qualification criteria plays an important role in the proper performance of the specific contract, while also achieving other objectives. The determination of qualification criteria is therefore an important aspect of the procurement system which must always be taken into account when changes are made to the procurement system.